Métodos y técnicas de maquillaje del Carnaval de Negros y Blancos, enfocados en el Colectivo Coreográfico Danzantes del Cerrillo. (2022)
Methods and techniques of facial makeup on the Blacks and Whites Carnival will be explained in this project; The focus of this work is based on the choreographic group Cerrillo dancers who have been evidenced and collected during the EAPEAT of the Andean Dance Chair 2018-1 where explore two makeups of many exhibitions of the choreographic group. (Cumbia party in the south and Labriegos paradise).